New Media Preferences in the Indian Advertising Industry: A Perspective on W eh Advertising Agencies and Marketers (Trinity Journal of Management, IT & Media (TJMITM), 2010)
Indian entertainment and media i11d11str.· ,s a  Ji1st groll'i11g sector of the Indian eco11,m;y a11d  tt 111cl11des the re1·e1111es /mm 1·ario11s media.  thm are tcle1·isio11. print. radio, film  cnre rrainment. out-of-home advertising, 11111sic 111d11srr:,. animation a11d gaming ind11stry (this  is 110\\ included in E&M sector, earlier it was  included i11 the lndian TT a11d Software  Re,·enues) and Online Advertising or New  Media Advertising. Advertisers today are  flooded \\ ith advertising options and  considerable thought is put iTllo deciding  ll'hich media must be chosen for the purpose  of nmning the adverllsing campaign. Since  most marketers today, have specified  advertising agencies who handle the media  buying and campaig11 pla11ning Ju11ction for  them, decisions regardi11g the budget  a/location onto vario11s media is usually taken  b\' markerers, in tandem with the professionals  from their respective advertising agn1cies. It  is therefore c rucial for the sales team of a11y  medwm( print or electro11ic) to be able to  convince the advertfaing agencies that a  campaign run on the medium would fetch f'.igh returns on investment for the adver//sed  brand. 111 light of this symbiotic rela1io11ship  between adverrismg agencies, advertisers a11d  various media vehicles, this paper explores the  altitude of advertisers as well as advertising  agencies towa,ds the efficacy of the new  medium- Internet. The paper further tries to  understand whether there is a discrepancy in  the media preferences of the advertisers and  the agencies a11d which media do ~ac/1 of these  groups consider more lucra11ve for _ ~he  purpose of run11ing brand led advertmng  campaigns.
Keywords: Internet Advertising; Indian Media; Indian Advertising; Advertising Agencies; Online Media